The Analysis Of Risk Assessment On Fiber Optic Production Line Using The Hazard Identification Risk Assessment And Determining Control (Hiradc) - Nina Tania Lestari (INTECOMS: Journal of Information Technology and Computer Science, 2024)
ABSTRACT The demand for optical fiber increases to meet the demands of Industry 4.0, companies that manufacture optical fiber must seize this moment to generate profitable business. However, let us not forget how important safety is to all employees working in the fiberglass industry, especially production employees who are directly involved in the fiberglass production process. This study focusses on Risk assessment for patch cords cables production using HIRADC method. The activities of Patch Cord Cable production are divided into 6 steps are striping, curing, trimming, crimping, inspection, packing. Risk assessment in the patch cord production process activities to the packing process by conducting a HIRADC Analysis from determining hazards, potential incidents, to risk ratings. The results of this study obtained additional control for recommended to eliminate the potential for work accidents in the activity Striping, Curing Trimming, Crimping, and Inspection to increase productivity production Cable Fiber Optic (item product: Patch Cord) in PT. JK aligns with SDG 9 that industrialization development can be achieved by improving manufacturing productivity by reducing or eliminating the possibility of occupational accidents. Keywords: Optical fiber, Risk Assessment, HIRADC, SDG